An Analysis of Barriers to the Implementation of an ISO Certified Quality Management System for National Meteorological and Hydrological Services in the Anglophone Caribbean - Cécil Mitchell; Bapon (SHM) Fakhruddin (Meteorological Applications, 2022)
Abstract Aeronautical Meteorological Offices under National Meteorological and Hydrological Service provide critical meteorological, hydrological, ocean and climatological information that sustain air navigation safety, efficiency, and regularity. Thus, to quality assure the information, the International Civil Aviation Organization recommended in 2002 that Aeronautical Meteorological Offices should implement ISO 9001 quality management system, which was subsequently standardized and became effective on 15 November 2012. There has been a slow movement towards adoption due to a number of barriers. In July 2019, 52% of Aeronautical Meteorological Offices commenced transition to the fifth iteration, ISO 9001:2015. A range of studies have investigated the barriers to successful quality management system implementation and certification within various organizations. However, only one study examined the Aeronautical Meteorological Offices and none of them covered the Anglophone Caribbean. Hence, the demography of the sample for this study is unique and this paper will contribute to filling the gaps in the literature. This exploratory study aims to identify the barriers, investigate their impacts, and propose recommendations to assist the Aeronautical Meteorological Offices to fully implement the ISO standard. Trinidad and Tobago Meteorological Service was selected as a case study due to its progress in the quality management system implementation and the scope of its operations. The study used and triangulated data collected from secondary sources (desktop research) and primary sources (survey and interviews). Seventeen barriers were identified and formed the new empirical framework for the Aeronautical Meteorological Offices in the Anglophone Caribbean. Most barriers were in the category of resources. The findings have significant implications for the policymakers, especially executive management, to address the barriers that are risks to sustainable quality management system.